Winnicott e a educação natural : a criança e a escola maternal - Corrêa, Fernanda da Silva (2011)
The present work aims to discuss report was the child s entry from zero to two years in the school context based on the thesis of Donald Winnicott, considered by many in the field of education and psychoanalysis a contemporary author. Also explain what you want out of their main ideas, is what the author thinks of child education and family relations (more precisely with the mother) and that the family and school must go to a good relationship with the professional education (teacher). Among different concepts wich guides the research is to Human Nature, wich the author explains encompasses the concepts and good enough mother holding following a natural education and act professional pedagogical education through play entered to family child. He uses the term nursery school instead of kindergarten. The study puts the concept of good enough mother, warm and satisfying, and holding between mother and child. Also investigates the relationship between teacher-student children aged zero to two years of age how the teacher accepts these questions,then,to address the ludic aspects of the child s admission to the school context front of the woman in the world of work